Classroom Interaction in Communicative Language Teaching of Public Secondary Schools in Nepal - Trilok Datt Tiwari (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Recently there has been a growing number of interests in classroom research primarily focusing on interaction and language learning as these two issues are considered to be essential components in communicative language teaching which is widely practiced today. This current study was aimed to find out the classroom interaction situation and factors affecting it in public Secondary schools of Kanchanpur district, Nepal. The participants of this study were three English language teachers teaching in the secondary level. The researcher used semi-structured interview and observation of video recordings of classes for collecting the data. In analyzing this study, the researcher used types of interaction proposed by Kumaravadivelu (2006) that include: interaction as textual activity, interaction as an interpersonal activity, and interaction as an ideational activity. The findings showed that all types of interaction activities proposed by him were present in the class. The study also revealed that the teacher often dominated, controlled and initiated the interaction. It further showed that there were several affective factors that prevented the teachers from having classroom interaction. The implication of the study is that the teachers should include all three types of interaction activities in the class and maximize group/pair work for effective teaching and learning of language.